Helminth parasites of South American fishes: Current status and characterization as a model for studies of biodiversity - Luque, Jose Luis (2017)
The South American subcontinent supports one of the world's most diverse and commercially very important ichthyofauna. In this context, the study of South American fish parasites is of increased relevance in understanding their key roles in ecosystems, regulating the abundance or density of host populations, stabilizing food webs and structuring host communities. It is hard to estimate the number of fish parasites in South America. The number of fish species studied for parasites is still low (less than 10%), although the total number of host-parasite associations (HPAs) found in the present study was 3971. Monogeneans, with 835 species (1123 HPAs, 28.5%), and trematodes, with 662 species (1127 HPAs, 30.9%), are the more diverse groups. Data gathered from the literature are useful to roughly estimate species richness of helminths from South American fish, even though there are some associated problems: the reliability of information depends on accurate species identification; the lack of knowledge about life cycles; the increasing number of discoveries of cryptic species and the geographically biased number of studies. Therefore, the closest true estimations of species diversity and distribution will rely on further studies combining both molecular and morphological approaches with ecological data such as host specificity, geographical distribution and life-cycle data. Research on biodiversity of fish parasites in South America is influenced by problems such as funding, taxonomic impediments and dispersion of research groups. Increasing collaboration, interchange and research networks in the context of globalization will enable a promising future for fish parasitology in South America.